Tinjauan hukum islam terhadap jual beli taqsith di toko baju bu iroh - Khomsin Mubarok; Ahmad Muhaini; Hari Widiyanto (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the implementation of bai' al-taqsith (installment sale) at Bu Iroh Clothing Store and examine its conformity with Islamic legal principles. The research employed a qualitative descriptive field research approach. Data were collected through observation, interviews, documentation, and literature review, and then analyzed using the perspectives of fiqh muamalah, the legal maxim al-'adah muhakkamah, and the concept of gharar. The findings reveal that the installment sale practice at Bu Iroh Clothing Store fulfills the essential pillars and requirements of a valid sale in Islamic law, including the presence of seller, buyer, object of sale, price, and mutual consent. The installment payment system is based on trust and local customs without a specifically determined repayment schedule. This practice can be classified as 'urf shahih (valid custom) and is consistent with the principle of al-'adah muhakkamah because it does not contradict Islamic legal principles. Although there is an element of uncertainty regarding the repayment period, it falls within the category of gharar yasir (minor uncertainty), which is tolerable and does not invalidate the contract. The study demonstrates that Islamic law is flexible in accommodating customary economic practices as long as they remain within the framework of Sharia principles.